2016
DOI: 10.1007/s12253-016-0165-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of CCND1 Gene c.870G>A Polymorphism with Breast Cancer Risk: A Case-ControlStudy and a Meta-Analysis

Abstract: Cyclin D1 (CCND1) plays an essential role in regulating the progress of the cell cycle from G1 to S phase. There is a common c.870G>A polymorphism in the CCND1 gene. The aim of this study was to investigate the association of CCND1 gene c.870G>A polymorphism with breast cancer risk in a case-control study, which followed by a meta-analysis and an in silico analysis. Three hundred and thirty-five subjects composed of 174 women with breast cancer and 161 healthy controls were included in the case-control study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Therefore, in this study we used bioinformatics software for analysing the molecular effects of IL‐1RA VNTR, and IL‐1α 4845G>T polymorphisms. Our data revealed that IL‐1RA VNTR alters RNA splicing pattern; furthermore, this issue could influence the gene expression (McManus & Graveley, ; Soleimani et al, ). According to Korthagen et al, (), IL‐1RA VNTR could affect the gene expression which can explain the role of this polymorphism in male infertility resulting from altered levels of IL‐1RA in the testis.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, in this study we used bioinformatics software for analysing the molecular effects of IL‐1RA VNTR, and IL‐1α 4845G>T polymorphisms. Our data revealed that IL‐1RA VNTR alters RNA splicing pattern; furthermore, this issue could influence the gene expression (McManus & Graveley, ; Soleimani et al, ). According to Korthagen et al, (), IL‐1RA VNTR could affect the gene expression which can explain the role of this polymorphism in male infertility resulting from altered levels of IL‐1RA in the testis.…”
Section: Discussionmentioning
confidence: 75%
“…These findings are further strengthened by another meta-analyses conducted by Lu et al (2009) [ 59 ] and Cui et al (2012) [ 60 ] that showed the association of AA genotype of CCND1 G870A polymorphism with breast cancer susceptibility. Similarly, Soleimani et al (2016) [ 61 ] showed a significant association between CCND1 G870A polymorphism and breast cancer risk but in Caucasians. A meta-analysis conducted Wen et al (2014) [ 62 ] supported our data that CCND1 G870A polymorphism is a potential risk factor in the development of esophageal cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Genetic alterations study with cBioportal revealed al terations of CCND1 in 35% of patient samples, with am plification as the highest alterations. Previous studies demonstrated that amplification in CCND1 is an early event in the development of a breast cancer stem cells (Burandt et al 2016), and mutations in CCND1 is associ ated with increased risk of breast cancer (Soleimani et al 2017). A previous study demonstrated that overexpression of CCND1 has occurred through amplification, transloca tion, or posttranscriptional regulation (Xu and Lin 2018).…”
Section: Discussionmentioning
confidence: 99%